Neue Bundesländer: Fortschritte bei der Verkehrsanbindung. - Sichelschmidt, Henning (Deutscher Verkehrs-Verlag, 2004)
Die Ausstattung der neuen Bundesländer mit Infrastruktur ist seit dem Ende der DDR in besonderem Maß Gegenstand öffentlichen Interesses gewesen. Erhebliche Mittel sind in ostdeutsche Verkehrsinfrastrukturprojekte geflossen. Der Beitrag versucht, die Fortschritte bei der Verkehrsanbindung der neuen Bundesländer deutlich zu machen und den verbleibenden Investitionsbedarf näher zu umreißen. difu

The paper analyses the infrastructure provision in East Germany. At the time of German unification 1990, infrastructure in East Germany was in a very bad condition. After more than ten years of rebuilding, most of the remaining need for infrastructure investments is probably in the road sector. Therefore, the planned new motorway connections to Mecklenburg-Western Pomerania as well as to Saxony-Anhalt and Thuringia will have to be completed and, furthermore, numerous defects of regional and local road networks will continuously have to be repaired. In the railway sector, improvements in the existing network (as far as they are justified by the prospective transport demand) are on the agenda whereas the planning of a new high-speed route Nuremberg-Erfurt has become doubtful for financial reasons. The least need for investments is left - after realization of current investment plans - in the airport sector. difu
Keywords: Verkehr; Verkehrsweg; Verkehrsinfrastruktur; Verkehrsanbindung; Erreichbarkeit; Verkehrsnetz; Schienenverkehr; Straßenverkehr; Flughafen; Binnenschiffsverkehr